Short-Time Suzuki Reactions of Arly Halides Catalyzed by Palladium-Loaded Nay Zeolite Under Aerobic Conditions - Durgun, Gülay; Artok, Levent (Izmir Institute of Technology, 2006)
The palladium-catalyzed Suzuki cross-coupling reaction is a powerful methods used in the synthesis of biaryl compounds.In this study, the Suzuki reactions of aryl bromides and chlorides with arylboronic acid were carried out over a Pd(NH3)42+-loaded NaY type zeolite. On the basis of our results, the Pd(NH3)42+-loaded NaY zeolite was found to be highly active for the Suzuki reactions of wide range of aryl bromides and electron poor aryl chlorides at low Pd concentrations (0.1-0.001mol %Pd), in air and at short times (5-45 minutes). The presence of relatively large amount of zeolite (1-4 g) was crucial for the success of the reactions with aryl chlorides. It was determined that there was a synergistic effect of the water- zeolite pair on the reaction rate.It was found that reactions were catalyzed dissolved palladium species. However,the palladium was largely recovered and only traces of palladium remained within the solution at the end of reaction (<0.8 ppm).
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2006
Includes bibliographical references (leaves: 71-81)
Text in English; Abstract: Turkish and English
xii, 131 leaves
Keywords: QD505 .D959 2006; Palladium catalysts; Heterogeneous catalysis